A New Type of Manganese Dioxide Car Air Conditioner Filter Element. Issue 3 (March 2021) - Liao, Minru; Sun, Haotian; Wang, Zehao; Xu, Xiaoyang; Qin, Cang
Abstract: Cars are already a daily necessity for every household. As a device that every car must install, the car air-conditioning filter is responsible for filtering the air inside and outside the car. The air passing through the pipe achieves clean air and protects the interior of the car. The purpose of personnel, but according to research, the air quality in close to 40% of cars is not up to standard. The China Consumers Association used the method of sampling statistics to sample 51 passenger cars as test samples, including 22 car brands including European, American, Japanese, Korean, and domestic. The results show that nearly 40% of vehicles do not meet the current air quality requirements for passenger cars. As a firewall to ensure clean air, car air-conditioning filters are constantly being developed and updated in order to meet the air quality requirements in the car. At present, the air-conditioning filter elements on the market are basically activated carbon filter elements, and the filtration performance is not satisfactory. Based on the traditional air-conditioning filter element, this paper designs an air-conditioning filter element with birnessite-type manganese dioxide as the core. The experiment shows that it is 15% better than the common single activated carbon air-conditioning filter element in adsorption efficiency and purification efficiency.